Determinants of labor shortage: With particular focus on the German environmental sector - Jens Horbach (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
Despite the ongoing discussion on labor shortage in the German economy there is still a lack of empirical analyses of this problem based on adequate econometric methods. The paper explores the determinants of labor shortage in the environmental sector supplying products and services that help to reduce environmental impacts and energy use. Labor shortages occur when the price adjustment mechanism is too slow to balance labor demand and supply. The empirical analysis of labor shortage uses recent data of the establishment panel of the Institute for Employment Research in Nuremberg. A descriptive analysis shows that the environmental sector seems to be over-proportionally affected by labor shortage. Following the results of an econometric analysis innovative firms are significantly more likely to be characterized by labor shortage problems. For climate protection technologies, analytics/consulting or environmental research and development labor shortage seems to result from the respective innovative activities of the firm s requiring high-skilled and specialized staff whereas labor shortage in the recycling sector is due to a lack of low-paid personnel. Further econometric estimations show that firms characterized by labor shortage problems are significantly more likely to pay wages above average. – – Trotz der andauernden aktuellen Diskussion über einen Fachkräftemangel in Deutschland besteht immer noch ein Mangel an empirischen Analysen auf der Basis ökonometrischer Methoden. Der Beitrag untersucht die Determinanten des Arbeits- bzw. Fachkräftemangels im Umweltsektor. Dieser Wirtschaftsbereich umfasst Produkte und Dienstleistungen, die dazu beitragen, Umweltschädigungen zu verringern oder den Energieverbrauch zu senken. Ein Mangel an Arbeitskräften kann auftreten, wenn der Preismechanismus zu langsam ist, um Nachfrage und Angebot am Arbeitsmarkt ins Gleichgewicht zu bringen. Die empirische Analyse basiert auf Daten des Betriebspanels des Instituts für Arbeitsmarkt- und Berufsforschung (IAB) in Nürnberg. Eine deskriptive Analyse zeigt zunächst, dass der Umweltsektor überproportional von einem Arbeitskräftemangel betroffen ist. Die Ergebnisse einer ökonometrischen Analyse belegen dann, dass dies insbesondere für innovative Umweltbetriebe zutrifft. Vor allem in den Umweltbereichen Klimaschutz, Analytik/Consulting und Umweltforschung und -entwicklung ist der Arbeitskräftemangel im Wesentlichen mit den Innovationsaktivitäten der Betriebe verknüpft, die hochqualifiziertes und spezialisiertes Personal benötigen. Der Arbeitskräftemangel im Recyclingsektor ist dagegen vor allem auf die geringe Verfügbarkeit sehr niedrig bezahlter Arbeitskräfte zurückzuführen. Weitergehende ökonometrische Schätzungen zeigen, dass Betriebe mit Fachkräftemangel überdurchschnittlich hohe Löhne zahlen.
Keywords: J23; J63; Q55; C35; 330; Labor shortage; environmental sector; bivariate probit model